Homozygous mutation in DNAAF4 causes primary ciliary dyskinesia in a Chinese family - Jiang, Guoliang; Zou, Lijun; Long, Lingzhi; He, Yijun; Lv, Xin; Han, Yuanyuan; Yao, Tingting; Zhang, Yan; Jiang, Mao; Peng, Zhangzhe; Tao, Lijian; Xie, Wei; et al. (Frontiers in Genetics, 2022)
Primary ciliary dyskinesia (PCD) is a rare autosomal recessive disorder that affects the structure and function of motile cilia, leading to classic clinical phenotypes, such as situs inversus, chronic sinusitis, bronchiectasis, repeated pneumonia and infertility. In this study, we diagnosed a female patient with PCD who was born in a consanguineous family through classic clinical manifestations, transmission electron microscopy and immunofluorescence staining. A novel DNAAF4 variant NM_130810: c.1118G>A (p. G373E) was filtered through Whole-exome sequencing. Subsequently, we explored the effect of the mutation on DNAAF4 protein from three aspects: protein expression, stability and interaction with downstream DNAAF2 protein through a series of experiments, such as transfection of plasmids and Co-immunoprecipitation. Finally, we confirmed that the mutation of DNAAF4 lead to PCD by reducing the stability of DNAAF4 protein, but the expression and function of DNAAF4 protein were not affected.